From personal advice to professional guidance, IDNLearn.com has the answers you seek. Get the information you need from our community of experts who provide accurate and comprehensive answers to all your questions.
Sagot :
To determine which equation models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds, we need to find an equation that satisfies the conditions provided: the weight is 9 inches below equilibrium at [tex]\( t = 0 \)[/tex] and returns to this position after [tex]\( t = 3 \)[/tex] seconds.
Given equations:
1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
Let's test each equation separately:
### 1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 3 \right) = -9 \cos(\pi) = -9 \times -1 = 9 \][/tex]
This does not match the condition at [tex]\( t = 3 \)[/tex] since we need [tex]\( d = -9 \)[/tex].
### 2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 3 \right) = -9 \cos(2\pi) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 3 \)[/tex].
### 3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
### 4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{2\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
Only the second equation [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex] satisfies the condition both at [tex]\( t = 0 \)[/tex] and [tex]\( t = 3 \)[/tex] seconds. Thus, the correct equation that models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds is:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} t \right) \][/tex]
Given equations:
1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
Let's test each equation separately:
### 1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 3 \right) = -9 \cos(\pi) = -9 \times -1 = 9 \][/tex]
This does not match the condition at [tex]\( t = 3 \)[/tex] since we need [tex]\( d = -9 \)[/tex].
### 2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 3 \right) = -9 \cos(2\pi) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 3 \)[/tex].
### 3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
### 4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{2\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
Only the second equation [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex] satisfies the condition both at [tex]\( t = 0 \)[/tex] and [tex]\( t = 3 \)[/tex] seconds. Thus, the correct equation that models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds is:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} t \right) \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.